The heretic's apprentice - Peters, Ellis, 1913-1995 (Peters, Ellis, 1913-1995. Chronicles of Brother Cadfael., 1990)
The sixteenth chronicle of Brother Cadfael. Brother Cadfael must find a rebuttal for charges of heresy and solve a murder.